The utilization of tire rubber strip as replacement of coarse aggregate in concrete - Chin Guan Yee (School of Environmental Engineering, University Malaysia Perlis, 2013)
One of the great environmental challenges facing nowadays is the disposal of worn out automobile tires. To overcome this global problem, several studies had been made to examine the various applications of recycled used tires including in the construction field. For example, the use of recycled rubber chips in asphalt concrete, thermal incineration of waste tires for the production of electricity or as fuel for cement kiln.